Hustlers and seekers how to crush it and find fulfillment-without losing your mind - Baker, Tommy (McGraw Hill, 2022)
"Get your hustle on-and find the emotional peace you seek-with a breakthrough motivational program. Chances are, you're one of two types of people: a Hustler, a Type-A go-getter driven by success; or a Seeker, a mindful person who craves emotional and spiritual fulfillment. But wouldn't it be ideal if you could combine these traits to attain the ultimate work-life balance? Now it's possible with this dynamic motivational guide by Tommy Baker, host of the popular podcast Resist Average Academy. With the COVID-19 pandemic forcing many of us to work from home, this balance is more necessary than ever. Drawing on over 300 firsthand interviews and on-the-ground experience, Baker equips you with the mindsets, concepts, and practical tools to find equal parts achievement and fulfillment. Baker offers hard-hitting, yet compassionate advice on: Bridging work ethic with time unplugged Cultivating ambition without losing sanity Being decisive and honing intuition Chasing down goals yet loving the process Introducing constraint to amplify creativity And ultimately, he offers advice on answering the age-old question: how do you know when it's time to put your foot on the gas or back off? With these tools, you can at once become the hustler and the seeker-and harness the powers of both for the success you desire"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Work-life balance; Ambition; Motivation (Psychology); Motivation; Conciliation travail-vie personnelle; Motivation (Psychologie)